Pengembangan Sistem Point of Sale Berbasis Web pada Toko Faafoo Menggunakan Framework Laravel - Dimas Ibnu Rahmadhani; Maryam Maryam (Universitas Methodist Indonesia, 2024)
The industrialized world has undergone significant changes thanks to technological developments. One example of the utilization of technological advances is in the buying and selling system. In the operation of the Faafoo shop, the seller still uses a manual system in transactions, namely by using a calculator as a payment calculation. The transaction process can be done quickly and accurately to save time and reduce the risk of errors by using a Point of Sale (POS) system. The POS system is built using the Laravel framework and implements Customer Relationship Management (CRM) to build and maintain mutually beneficial relationships with customers. POS system development uses the Agile Method which has the advantage of being adaptable and flexible to changing user needs and uses Black Box Testing and Usability Testing with the System Usability Scale (SUS) method for system testing. The results of blackbox testing show that the system is able to meet all the requirements set and function correctly. In addition, the results of the SUS (System Usability Scale) test which obtained a final score of 75.5 showed that the system received an